1995
DOI: 10.1111/j.1600-0536.1995.tb00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational contact dermatitis in bakers, confectioners and cooks

Abstract: A population-based study was performed to investigate incidence rates of occupational skin disease (OSD) in bakers, confectioners and cooks, as well as the rôle of endogenous and exogenous risk factors. In North Bavaria, all closed cases of OSD were recorded systematically in a 3-year period and the total number of employees in the food industry was known over the same period of time. Incidence rates of OSD and relative risks of atopic skin diathesis (AD) and respiratory atopy (RA) were calculated. The overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
59
0
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 25 publications
5
59
0
4
Order By: Relevance
“…These findings are in accordance with recent results from industry-based cohort studies and register-based studies in which increased incidences of eczema were mainly found in younger age groups (1,(3)(4)(5)(6)(7). However, none of these studies was done prospectively in the general population or took into account exposure in holiday jobs.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…These findings are in accordance with recent results from industry-based cohort studies and register-based studies in which increased incidences of eczema were mainly found in younger age groups (1,(3)(4)(5)(6)(7). However, none of these studies was done prospectively in the general population or took into account exposure in holiday jobs.…”
Section: Discussionsupporting
confidence: 81%
“…The latter studies have indicated that even short exposure periods may contribute to the development of skin diseases (1,(3)(4)(5)(6)(7). Such industry-based studies provide valuable information on the incidence and time course of eczema in one specific industry but cannot be generalized to the general population.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…One population-based study (3) indicated a significantly higher prevalence of hand eczema among female cleaners (22%) than in other occupations, and several other studies report a high risk of hand eczema in this type of work (24,32). Food handling and bakery work are other risk areas with a high occurrence of hand eczema, especially among women (11,33). Nursing involves extensive wet work, and the sector predominantly employs women.…”
Section: High-risk Occupationsmentioning
confidence: 99%